Genetic and environmental effects affecting the variation in birth date and birth weight of reindeer calves - Muuttoranta, Kirsi; Holand, Øystein; Røed, Knut H.; Tapio, Miika; Nieminen, Mauri; Mäki-Tanila, Asko (Rangifer)
2013